Normal values of hertel exophthalmometer in healthy syrian adults - رجب محمود; زهره خالد (Latakia University Journal -Medical Sciences Series, 2022)
Purpose: to determine normal exophthalmometric values (EVs) in Syrian healthy adults and its relation with age, gender, inter-orbital distance (IOD) and palpebral fissure height (PFH). Materials and Methods: a cross sectional study includes 402 syrian healthy adults, they divided by age into two groups: the first one with ages (18-40) and the second with ages (41-60), a mirror hertel exophthalmometer was used to measure exophthalmometric values and inter-orbital distance, a ruler was used to measure palpebral fissure height. Results: mean absulute exophthalmometric value (AEV) of whole sample is 15.79 ± 2.1 with range of 11-22 mm , mean relative exophthalmometric value of whole sample is 0.53± 0.55 with range of 0-2 mm , mean (AEV) of first group (15,99±1.8) and second group (15.51±1.75) are statically different (p-value=0.01) , (AEV) is negatively correlated with age in second group (fifth and sixth decades), (AEV) is positively correlated with (IPD) and (PFH), mean (AEV) is not statically different between right and left eyes or males and females in two groups of this study, spherical refractive errors between ±3.00 diopters have no statically effect on (AEV). Conclusion: normal (AEV) is negatively correlated with age and positively correlated with (IOD) and (PFH), mean (AEV) of males and females are not statically different.